Hatching Induction of Cyst Nematodes in Bare Soils Drenched With Root Exudates Under Controlled Conditions - Ngala, Bruno; Mariette, Nicolas; Ianszen, Mélina; Dewaegeneire, Pauline; Denis, Marie-Christine; Porte, Catherine; Piriou, Christophe; Robilliard, Emilie; Couetil, Antoine; Nguema-Ona, Eric; Yvin, Jean-Claude; Gobert, Virginie; et al. (Frontiers in Plant Science, 2021)
Cyst nematodes account for substantial annual yield losses in crop production worldwide. Concerns over environmental and health issues due to the use of chemical nematicides mean alternative sustainable and integrated solutions are urgently required. Hatch induction of encysted eggs in the absence of host plants, i.e., ‘suicide-hatching,’ could be a sustainable alternative in reducing population densities of cyst nematodes in infested soils. Here we examined in situ hatching of encysted eggs of Globodera pallida, Heterodera carotae, and Heterodera schachtii at varying soil depths, following exogenous applications of host root exudates in repeated glasshouse experiments. Cysts were retrieved 30 or 43 days post-incubation depending on the nematode species and assessed for hatching rates relative to the initial number of viable eggs per cyst. Hatching of the potato cyst nematode G. pallida depended on both soil moisture and effective exposure to root exudates, and to a lesser extent on exudate concentration. The carrot cyst nematode H. carotae had over 75% hatched induced by root exudate irrespective of the concentration, with better hatch induction at 20 cm as compared with 10 cm soil depth. Hatching of the beet cyst nematode H. schachtii largely depended on the soil moisture level at constant temperature, rather than the type or concentration of root exudates applied. As a conclusion, exogenously applied host root exudates may play a major role in inducing in situ hatch of encysted eggs of potato and carrot cyst nematodes in the absence of host plant under favorable soil temperature/moisture conditions. To improve such strategy, the characterization of chemical profiles of the root exudate composition and field validation are currently ongoing.